Adopsi Literasi Fintech untuk E-Money di Kalangan Generasi Z - Yuliawati, Tia; Hendrayati, Heny; Cintyawati, Cici; Furqon, Chairul (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to determine and analyze the effect of fintech literacy on actual usage of electronic money in Generation Z, as well as to determine and analyze the influence of perceived ease of use, perceived usefulness, and personal innovativeness on actual usage of electronic money in Generation Z. The method used in this study is a survey method with a verification approach. Where data is collected from a sample of 100 respondents through a questionnaire distributed through Google Form. Hypothesis testing is done using SEM Analysis with the help of SmartPLS 3.0 software. The results show that fintech literacy has a positive and significant effect on actual usage of electronic money. Perceived ease of use and perceived usefulness have no significant effect on actual usage of electronic money, while personal innovativeness has a positive and significant effect on actual usage of electronic money. Personal innovativeness is also known to be a factor that has the greatest influence on actual usage of electronic money in Generation Z. This research has implications for the development of management science, especially to see the effect of fintech literacy on actual usage of electronic money that can be used by the financial services sector as a basis for decision making.